Peran mahasiswa PAI sebagai agen perubahan: Upaya mengintegrasikan nilai Spiritual dan Self-Regulation dalam menjawab tantangan kecemasan akademik generasi Z - Indriany, Hafizah; Patimah, Siti; Puspika Sari, Herlini (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2025)
The phenomenon of academic anxiety among Generation Z is increasing in line with academic pressure, digital competition, and weak spiritual foundations. This article aims to analyze the role of Islamic Education (PAI) students as agents of change in integrating spiritual values and the concept of self-regulation as a solution to academic anxiety. This study uses a qualitative approach with literature analysis from accredited national and international journals. The results of the discussion show that Islamic spiritual values such as patience, tawakkal, dzikir, and muhasabah can strengthen inner peace, while the concept of self-regulation helps students manage their emotions, motivation, and learning behavior systematically. The integration of the two produces a religious-psychological learning model that is not only effective in reducing anxiety levels but also improves students' academic and spiritual well-being. In conclusion, PAI students play a strategic role as agents of change by setting an inspiring example of spirituality and self-regulation for the younger generation in facing academic challenges in the era of globalization.